The Experience of 99mTc-Al2O3 Using for the Detection of Sentinel Lymph Nodes in Cervical Cancer Patients; European Journal of Nuclear Medicine and Molecular Imaging; Vol. 43, suppl. 1 : European Association of Nuclear Medicine, EANM'16 : Annual Congress, October 15-19, 2016, Barcelona, Spain : abstracts - Chernov V. I. Vladimir Ivanovich; Sinilkin I. G. Ivan Gennadjevich; Medvedeva А. А. Anna Aleksandrovna; Zelchan (Zeltchan) R. V. Roman Vladimirovich; Lyapunov A. Yu. Aleksandr Yurjevich; Bragina O. D. Olga Dmitrievna; Chernyshova A. L. Alena Leonidovna; Kolomiets L. A. Larisa Aleksandrovna; Skuridin V. S. Viktor Sergeyevich (2016, 2016)
Title screen